IDENTIFYING ETHICAL DILEMMAS OF PORTUGUESE CHARTERED ACCOUNTANTS - Silva, Amélia (2016)
The way professionals deal with ethical dilemmas and the decisions they make may be guided by a personal and individual ideology, but it is also strongly influenced by their professional group and society. This paper focuses in real situations as they are experienced by individuals in their day-to-day professional life. The data were collected using opened-end interviews. Respondents were asked to identify the ethical dilemmas they had been faced with during their professional life. Qualitative analysis shows that main dilemmas are about how to deal with “informal economy”, “false invoices” and “tax evasion”. This study aims to contribute to the discussion of ethical issues faced by Portuguese Chartered Account (TOC), thus promoting a large debate about the way the TOC can help to create a better society and consequently legitimating their existence as a professional organization of public interest. More than ever, understanding professionals’ behavior in their real context is essential for to build a culture conducive to the ethical development of society, and to ensure, at the same time, the desirable business sustainability. This study gives a broaden description of ethics dilemmas faced by chartered accounts and shows some inefficiency in the ethical control system made by professional bodies.